Risk factors for hemorrhage of brain arteriovenous malformation - Shaligram, Sonali S. (CNS Neurosci Ther, 2019)
Patients with brain arteriovenous malformation (bAVM) are at risk of intracranial hemorrhage (ICH). Overall, bAVM accounts for 25% of hemorrhagic strokes in adults <50 years of age. The treatment of unruptured bAVMs has become controversial, because the natural history of these patients may be less morbid than invasive therapies. Available treatments include observation, surgical resection, endovascular embolization, stereotactic radiosurgery, or combination thereof. Knowing the risk factors for bAVM hemorrhage is crucial for selecting appropriate therapeutic strategies. In this review, we discussed several biological risk factors, which may contribute to bAVM hemorrhage.